(untitled) (Journal of the College of Basic Education, 2025)
This research dealt with a study on (expressive works between American and European contemporary porcelain comparative analytical study) and came from four chapters ofthe first on the systematic framework of research, which includes the problem that lies in (what are the works andformulations produced by both American and contemporary European porcelain). The purposeof this study was todetect expressive works between American and European ceramics. The borders were spatial: America and Europe, temporal: (1950-1980) The terminology seeker also knew in the nature of the current research: (work, expressionism) linguistically, philosophically and procedurally. The researcher then moved on to the second chapter, which included three investigations and addressed the first: 1- Expressionism: Includes the Bridge Group, the Blue Knight Group, the expressive qualities, the most important artists of the expressive school, then Nazi art and expression, the entry into abstract expressionism, the emergence of abstract art, and the influence of Jackson Pollock in contemporary art, Then move on to the second research: 2- Contemporary American Porcelain: And then move on to the third research: 3- Contemporary European porcelain: the researcher touched on ... 1- Contemporary British Porcelain 2- Contemporary Italian Porcelain 3- Contemporary German Porcelain 4- Contemporary French Porcelain From these investigations, the researcher extracted indicators of the theoretical framework, and moved to the third chapter of the research procedures in the research community, the research sample, the research tool and the research method. Then chapter four included the results and conclusions and all the following were: 1- Technical expression of ideas that are in the process of researching a subject of some of the technique in place perceptibly and the possibility of knowledge and access to the concepts of technology. 2- Abstract works appeared in the concept of changing shape, abolishing job performance and going to aesthetic and artistic orientation. 3- Use colors in America (red- orange- blue - green - and lead), such as sample (1-2-3). 4- Use colors in European countries (black- white, lead, olive- orange), such as sample (4-5-6-7). 5- Use mattresses to draw some works in random abstract lines as in a sample (1-5-7). 6- Carry out works in the geometric style to reveal his pottery with an integrated unit of form and content as in the sample (6-7).